Strategi Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran di MTsN Kabupaten Lampung Utara Melalui Pengembangan Kompetensi Profesional Guru - Nurdin, Rahmawati; Pahrudin, Agus; Thahir, Andi (STIES ALIFA, 2022)
This study aims to investigate the strategies used by school principals in improving the quality of learning in the State Madrasah Tsanawiyah (MTsN) of North Lampung Regency through developing teachers' professional competencies. The quality of education is strongly influenced by teachers' qualifications, competence, and dedication in carrying out their professional duties. Principals have a very important role as leaders who can influence, motivate and guide teachers to achieve the desired educational goals. This study used a qualitative approach with a focus on describing and analyzing the phenomenon under study. Data were collected through in-depth interviews with principals and teachers, observations, and document studies. The research was conducted in three MTsN in North Lampung District. The results showed that there are various strategies implemented by principals to improve teachers' professional competence. These strategies can be divided into formal and informal activities. Formal activities include participation in seminars, workshops, training, and coaching organized by the Ministry of Religious Affairs, MGMP, madrasah external mentors, and madrasah supervisors. In addition, non-formal activities such as experience-sharing sessions are also organized to facilitate the exchange of knowledge and experience between teachers. The study also identified several obstacles faced by principals in developing teachers' professionalism, such as limited mastery of technology, limited teacher creativity, and the lack of scientific research conducted by teachers. Overall, the role of school principals is very significant in improving the quality of learning at MTsN in North Lampung Regency. Through appropriate strategies, both through formal and informal activities, as well as overcoming the obstacles faced, principals can help improve teachers' professional competence and overall learning quality.